PELATIHAN PEMANFAATAN MATRIKS BOSTON CONSULTING GROUP DALAM ANALISIS STRATEGI BISNIS USAHA KONVEKSI - Ekadjaja, Margarita; Tjandra Bravo, Christiandinata (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The dynamics of society require business people to be flexible and creative in designing business strategy plans. PKM's activity partner is a family company whose business is convection with several production lines called CMT. Mitra, as a family company that has various types of products and business lines, experiences difficulties in analyzing which business lines are profitable and should be developed. As a solution to partner problems, the PKM FEB UNTAR Team socialized the use of the Boston Consulting Group (BCG) matrix as a technique for analyzing business strategy decision making based on quadrant positions which include question marks, stars, cash cows and dogs. Socialization is provided in the form of offline training at partner business locations. The results obtained from the four partner production lines, namely uniforms, screen-printed t-shirts, bedding and party clothes, only the uniform production line is in a position that can still be maintained because in this position there is relatively a lot of cash and does not require large costs. However, on the contrary, with screen-printed t-shirt, bedding and party clothes production lines, partners have to re-evaluate their business and have to restructure for the sustainability of the partner's business. In this position, the partner production line has a low market share and does not have the potential to generate much cash.